Rocking of single-layer armour units measured by embedded sensors - Hofland, Bas; Houtzager, Daan; Caldera, Ganga; Antonini, Alessandro; van Gent, Marcel; Bakker, Pieter; van der Lem, Cock (Journal of Coastal and Hydraulic Structures, 2023)
Single layer randomly placed armour units are used in many rubble mound breakwaters around the world. For these armour layers first extraction of units starts at high loads and can then progress quickly. Before the first extraction of a unit, typically no quantitative description of damage can be given. But additional to extraction, breakage of armour units due to rocking could be a major damage mechanism. This paper treat novel embedded Rocking Sensors. The technique is used to obtain the first measurements of rocking-impact velocities of single-layer units. They are also the first tests where the instrumented units can naturally move with the compacting layer during storm build-up. Physical model tests were performed on an armour layer with XBloc units. With 8 to 10 instrumented units per test run, in total 640 single measurements of the rocking motion of a unit during a 1200 wave test run were obtained, for three water levels and five wave heights. From the Rocking Sensors the number of impacts and rotational impact velocities were obtained. From an image analysis the along-slope settlement of the units during the tests was quantified. The rotational motion expressed by was found to be most convenient to express the motion. It can be seen that the units in the armour layer rock much more often than visually observed. Settlement seems to be a continuous progress, with most units rocking intermittently. Highest impact velocities are seen to occur around the water line, and in the uprush phase of the waves. A maximum impact velocity for all tests of 0.34 m/s (model scale) was measured. A preliminary design expression for rocking impact velocities of single layer units (Xblocs) is given. The paper shows that novel measurement techniques like the Rocking Sensors and vision techniques can and should be used to quantify damage mechanisms to rubble mound single-layer armour, additional to counting the extracted number of intact units.